Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1093/treephys/tpaa137
|View full text |Cite
|
Sign up to set email alerts
|

Sap flow, xylem anatomy and photosynthetic variables of threePerseaspecies in response to laurel wilt

Abstract: Laurel wilt, a lethal vascular wilt disease caused by the fungus Raffaelea lauricola, affects several tree species in the Lauraceae, including three Persea species. The susceptibility to laurel wilt of two forest tree species native to the southern United States, Persea borbonia and Persea palustris, and avocado, Persea americana cv Waldin, was examined and related to tree physiology and xylem anatomy. Net CO2 assimilation (A), stomatal conductance (gs), leaf chlorophyll index (LCI), leaf chlorophyll fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Upon initial infection, H. lauricola conidia travel through the xylem, triggering the host tree to launch a series of defensive responses, appearing similar to a drought stress response (Castillo‐Argaez, Schaffer, et al, 2020). These defences include secretion of resins and formation of tyloses (outgrowths of parenchymal cells into the xylem vessels) in an attempt to restrict transport of the foreign fungus (Castillo‐Argaez, Vazquez, et al, 2020); however, this response eventually blocks xylem vessels, resulting in systemic wilt and ultimately tree mortality (Inch et al, 2011). Susceptible trees begin to show symptoms within 2 weeks after infection and can die as early as 4 to 6 weeks post‐infection (Hughes et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…Upon initial infection, H. lauricola conidia travel through the xylem, triggering the host tree to launch a series of defensive responses, appearing similar to a drought stress response (Castillo‐Argaez, Schaffer, et al, 2020). These defences include secretion of resins and formation of tyloses (outgrowths of parenchymal cells into the xylem vessels) in an attempt to restrict transport of the foreign fungus (Castillo‐Argaez, Vazquez, et al, 2020); however, this response eventually blocks xylem vessels, resulting in systemic wilt and ultimately tree mortality (Inch et al, 2011). Susceptible trees begin to show symptoms within 2 weeks after infection and can die as early as 4 to 6 weeks post‐infection (Hughes et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…As several previous studies suggest, the survival of infected trees appears to be connected with the size of the vessels [ 45 , 46 , 47 ]. An assessment of constitutive traits, such as vessel characteristics before or at the time of infection, is needed and should be supplemented with the study of induced responses in cambial activity and the production of new vessels that were differentiated under specific stimuli.…”
Section: Discussionmentioning
confidence: 79%
“…Contrary to the genus Ulmus , species of the genus Persea have diffuse-porous wood forming same-sized vessels during the entire growing season. Although the vessels are larger and more prone to become severely invaded by fungi, the remaining vessels may substitute large ones to maintain optimal water transport capacity [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, as a consequence of accumulation of tyloses and gums, xylem vessels get blocked and hinder the water conductance that decreases xylem sap flow; this adversely affects leaf gas exchange (Ploetz et al, 2015). Castillo-Argaez et al (2021) found that, in three species of Persea sp., about 50% of xylem vessels were clogged by tyloses accumulation as a result of laurel wilt infection. Also, in the same study, they observed different symptoms like branch dieback, leaf wilting, and discoloration of sapwood which attributed to the embolisms, and were also the consequence of tyloses blockage.…”
Section: Fungal Dimorphismmentioning
confidence: 99%
“…Castillo‐Argaez et al. (2021) found that, in three species of Persea sp., about 50% of xylem vessels were clogged by tyloses accumulation as a result of laurel wilt infection. Also, in the same study, they observed different symptoms like branch dieback, leaf wilting, and discoloration of sapwood which attributed to the embolisms, and were also the consequence of tyloses blockage.…”
Section: H Lauricola Virulencementioning
confidence: 99%